Painleve analysis of travelling wave solutions and analysis of energy estimates for a nonlinear Sobolev-type equation - A. I. Aristov (Учёные записки Казанского университета: Серия Физико-математические науки)
There is considerable interest in studying unbounded solutions of nonlinear partial equations. In many cases, energy estimates can be used to prove that the solution tends to infinity in finite time, while also providing an estimate for the latter. Here, an equation in which energy estimates fail to gauge the cases when solutions exhibit such behavior was analyzed. A class of unbounded solutions was explored using the Painleve analysis.